The Role of Transformational Leadership in Increasing Work Motivation of Millennial Generation Employees - Andi Kurniawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to analyze the role of transformational leadership in increasing work motivation of millennial generation employees through qualitative literature synthesis of relevant scientific journal articles. Transformational leadership, with its dimensions of Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration, is identified as a relevant leadership style in dealing with the unique characteristics and expectations of millennials in the workplace. The research method involves text extraction from the analyzed articles, thematic content analysis, and integrative synthesis to build arguments. The results of the analysis indicate that transformational leadership consistently has a positive effect on work motivation and related outcomes such as satisfaction, performance, and innovation. The dimensions of transformational leadership were found to be highly aligned with millennial motivational needs, such as the search for meaning in work, self-development, intellectual challenge, and authentic work relationships. Transformational leaders are able to create an inspiring, empowering, and growth-supportive work environment, which effectively motivates millennial employees. Practical implications include recommendations for leadership development, millennial talent management strategies, and organizational culture design. Limitations of the study lie in the reliance on secondary sources and the lack of millennial-specific primary data in the sources analyzed. Further research is suggested to focus on primary empirical studies on the millennial population.